Cobalt Phosphide Modified Titanium Oxide Nanophotocatalysts with Significantly Enhanced Photocatalytic Hydrogen Evolution from Water Splitting. Issue 14 (2nd February 2017) - Yue, Xinzheng; Yi, Shasha; Wang, Runwei; Zhang, Zongtao; Qiu, Shilun
Abstract : Production of hydrogen from photocatalytic water splitting holds promise as an alternative energy source with superiority of cleanliness, environment friendliness, low price, and sustainability. Perfectly constructing the noble‐metal‐free and stable hybrid structure photocatalyst is quite essential; herein, for the first time the authors aim to use cobalt phosphide as the cocatalyst on titanium oxide to form a novel hybrid structure to enhance the utilization of the photoexcited electrons in redox reactions for improved photocatalytic H2 evolution activity. Thus, the achieved significantly increased photocatalytic H2 ‐evolution rate on the optimized CoP/TiO2 (8350 µmol h −1 g −1 ) is 11 times higher than that of the pristine TiO2 . Moreover, this work is expected to spur more insight into synthesizing such novel photofunctional systems, achieving high photocatalytic H2 evolution activity and sufficient stability for solar‐to‐chemical conversion and utilization. Abstract : For the first time, a novel CoP/TiO2 hybrid nanophotocatalyst is successfully constructed, exhibiting high separation of photoexcited charge carriers and retarding the recombination of electron–hole pairs, excellent photocatalytic H2 evolution performance, and sufficient photostability. The obtained structure as photocatalysts has advantageous factors for both the material and structure, and achieves significantly enhanced photoconversion efficiency.